Устройство для крепления стержней-подложек в реакторе выращивания поликристаллического кремния - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бараков Б. Н. Борис Николаевич; Прочанкин А. П. Александр Петрович; Муравицкий С. А. Степан Александрович; Стенин А. А. Александр Александрович; Никулин А. И. Анатолий Иванович
опубл. 27.08.10